TESTING THE FACTORS THAT CAUSE HERDING BEHAVIOR ON THE INDONESIAN STOCK MARKET - Talebong, Kevin; Pagalung, Gagaring; Afdal, Afdal (Department of Accounting, Faculty of Economics & Business, Universitas Diponegoro, 2024)
This study aims to examine and analyze the effect of stock return, market capitalization, and information asymmetry on herding behavior. The data used are secondary data obtained from the annual report of the company that is the object of research. The population in this study is all companies whose shares are listed in the LQ45 stock index for 2020-2022. Sample selection using purposive sampling and data analysis was carried out by multiple linear regression analysis. The results showed that stock returns had an effect in triggering herding behavior, while market capitalization and information asymmetry had no effect on triggering herding behavior. However, stock return, market capitalization, and information asymmetry together affect herding behavior.